2015
DOI: 10.1371/journal.pone.0132347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculation with Glomus versiforme on Cadmium Accumulation, Antioxidant Activities and Phytochelatins of Solanum photeinocarpum

Abstract: The plant growth, phosphate acquisition, Cd translocation, phytochelatins (PCs) production and antioxidant parameters [superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (POD), ascorbate peroxidase (APX), glutathione reductase (GR), glutathione (GSH), ascorbate (ASA) and malonaldehyde (MDA)] were investigated in Cd-hyperaccumulator Solanum photeinocarpum inoculated with Glomus versiforme BGC GD01C (Gv) in Cd-added soils (0, 5, 10, 20, 40 mg Cd kg-1 soil). Mycorrhizal colonization rates were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 62 publications
4
14
0
Order By: Relevance
“…Other studies, largely in greenhouses, have typically found that metals decrease AMF colonization and/or diversity (del Val et al 1999a,b; Khan 2001; Chen et al 2005), although Diaz et al (1996) and Tan et al (2015) found no effect of applied Zn, Pb, or Cd solutions on AMF colonization of three host plants, and Vogel-Mikus et al (2006) found that increasing soil Cd and Pb by mixing contaminated and uncontaminated soils in different ratios increased AMF colonization of the hyperaccumulator Thlaspi praecox . Reported effects of AMF colonization on plant metal uptake are similarly inconsistent (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies, largely in greenhouses, have typically found that metals decrease AMF colonization and/or diversity (del Val et al 1999a,b; Khan 2001; Chen et al 2005), although Diaz et al (1996) and Tan et al (2015) found no effect of applied Zn, Pb, or Cd solutions on AMF colonization of three host plants, and Vogel-Mikus et al (2006) found that increasing soil Cd and Pb by mixing contaminated and uncontaminated soils in different ratios increased AMF colonization of the hyperaccumulator Thlaspi praecox . Reported effects of AMF colonization on plant metal uptake are similarly inconsistent (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…AMF can stimulate plant growth by increasing nutrient uptake 16 17 , supply a HM isolation belt to protect plant from HM toxicity, and reduce the absorption of HM by plants through secreting organic compounds (e.g., glomalin) in the soil to chelate HM ions 18 19 . Moreover, AMF could increase the activities of antioxidative system under HM stress 20 21 , and some genes with presumptive roles in alleviating oxidative stress were found in AMF 22 . However, the overall mechanisms by which AMF alleviate HM phytotoxicity have still been not completely understood, with controversial outcomes depending on the interactions of specific plant, fungus and HM species.…”
mentioning
confidence: 99%
“…The best results were obtained when mycorrhiza and putrescine were treated together for alleviation of Cd toxicity in sorghum. Mycorrhizal plants along with putrescine displayed lower lipid peroxidation and low hydrogen peroxide production [40,[54][55][56]. It is widely accepted that diminishing levels are one of the mechanisms by which AM protects plants against diverse stresses [57][58][59].…”
Section: Discussionmentioning
confidence: 99%